Belarusian regional journalism in the context of digital development - Hradziushka А.А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article discusses the work of the regional media of the Republic of Belarus in the digital environment. The material for the study was the websites of regional and district newspapers, as well as their accounts in social networks and instant messengers. The main strategies for organizing the work of editorial offices in the context of digital development are identified. The key indicators of digital media audience involvement are considered. The growth of the influence of social networks, recommendation services, search engines on the regional media landscape is shown. The authors argue that under the dominance of the Big Three social platforms (Instagram, Telegram and TikTok) in the market the media find new ways to distribute news, relevant formats for interacting with readers. The results of a survey of chief editors are given. The main models of digital transformation of the local media space are systematized. The author comes to the conclusion that the main metric of the work of journalists of regional media in the context of digitalization is the involvement of the audience.